Gastroprotective effects of melastoma malabathricum aqueous leaf extract against ethanol-induced gastric ulcer in rats - Hussain, F.; Ali, Hapipah Mohd; Ismail, S.; Noor, S.M.; Abdulla, M.A. (2008)
The gastro-protective effects of the aqueous leaf extract of Melastoma malabathricum was investigated against ethanol-induced gastric mucosal injuries in rats. There were four groups of adult sprague dawley rats, consisting of six rats per group. Macroscopically, oral administration of absolute ethanol to rats that had been pre-treated with only distilled water significantly produced extensive lesions of the gastric mucosa. Oral pre-treatment with either 250 mg kg-1 of M. malabathricum extract, 500 mg kg-1 of M. malabathricum extract, or 20 mg kg-1 of omeprazole 60 minutes before administration of absolute ethanol significantly reduced the formation of gastric mucosal injuries. The observed protection was significant and dose dependent in inhibiting ethanol-induced gastric ulcers. Microscopically, rats that had been pre-treated with only distilled water showed marked damage of the gastric mucosa, induced submucosal edema and leucocytes infiltration. However, animals that had been pre-treated with aqueous leaf extracts or omeprazole showed marked reduction of gastric mucosal damage, reduction of oedema and less leucocyte infiltration of submucosal layer. The results indicated that 500 mg kg-1 aqueous leaf extract of M. malabathricum provided the best protection to the gastric mucosa in rats against ethanol-induced gastric ulcers. © 2008 Science Publications.